Upaya Meningkatkan Hasil Belajar Sejarah Menggunakan Metode Pembelajaran Artikulasi pada Siswa Kelas X TKJ 1 SMK Taman Siswa Bandar Lampung - Jaya, Wayan Satria; Febrianti, Aurora Nandia; Ranti, Ranti (STKIP PGRI Bandar Lampung, 2023)
The main problem is the residual learning outcomes that are less than optimal, to improve learning outcomes, teachers must be able to use interesting and innovative learning models such as the Articulation learning model. The purpose of this study was to determine the increase in history learning outcomes by using the Articulation learning model in class X TKJ I even semester SMK Tamansiswa Teluk Betung. This type of research is classroom action research (CAR). The subjects in this study were 22 students of class X TKJ I at SMK Tamansiswa Teluk Betung. Classroom action research was conducted in 2 cycles, each cycle consisting of three meetings consisting of several stages, namely planning, implementing, observing and reflecting. The instruments used in this study were observation sheets, written tests and documentation. From the results of this study it can be concluded that (1) Student activity in applying the Articulation learning model during cycles I and II experienced an increase where in cycle I it reached 72% and in cycle II it reached 92%. (2) Student learning outcomes after the implementation of the Articulation learning model experienced a very good increase. In the pre-cycle, the percentage of learning completeness was 45.45%, then it increased in cycle I by obtaining a percentage of learning completeness of 68.82% and in cycle II, the percentage of learning completeness was 86.36%. From these results it can be concluded that using the Articulation learning model can improve history learning outcomes in class X TKJ I SMK Tamansiswa in the 2022/2023 academic year.